Pathological drivers of coral diseases across the Arabian Peninsula - Thierry M. Work; Greta S. Aeby; David Abrego; Jessica Bouwmeester; Emily Howells; Pedro Range; Maren Ziegler; Thor Jensen; Amanda Shore; Grace Vaughan; John A. Burt; Christian R. Voolstra; et al. (Coral Reefs, 2026)
Increasing trends of coral mortality are a challenge to coral reef management worldwide, and a need exists to identify the causes and pathways involved. Pathology is useful to help decipher potential causes of mortality in animals, because it illuminates agents associated with lesions and gives insights on the nature of how a host responds to said agents. To better understand the nature of threats facing corals in the Arabian Peninsula, we performed gross and microscopic pathology on corals from Saudi Arabia, Qatar, and the United Arab Emirates. Among 321 coral fragments examined from 21 genera, tissue loss was the most common lesion seen in 31% of samples, reflecting its widespread presence on reefs from the Arabian Peninsula. Histologically, 68% of lesions exhibited necrosis, predominantly in the basal body wall and surface body wall. Endolithic filamentous microalgae and sponges, originating from the skeleton, were associated with 57% and 39% of lesions, respectively, and were often linked to necrosis and hyaline membrane formation. Cell-associated microbial aggregates and coccidia were detected mainly in Acropora, Pocillopora , and Porites but were not associated with adverse host response. Notably, 69–100% of fragments showing lesions were female likely reflecting the temporal reproductive life history of corals in the region. Our findings highlight endolithic organisms as major contributors to coral tissue degradation in the Arabian Peninsula. Future studies might focus on drivers of endolithic microalgal and sponge dynamics in the region and their role in coral reef health.

Exploring development of spatially stratified wind turbine collision risk prior distributions for eagles: An application of adaptive management - Paige E. Howell; Leslie New; Emily R. Bjerre; Hillary M. White (Journal of Environmental Management, 2025)

Estimated golden eagle mortality from wind turbines in the western United States - Jay V. Gedir; Matthew J. Gould; Brian A. Millsap; Paige E. Howell; Guthrie S. Zimmerman; Emily R. Bjerre; Hillary M. White (Biological Conservation, 2025)

Practical methods for the control of tor-grass (Brachypodium pinnatum s.l.) and the restoration of calcareous grassland - Lucy E. Ridding; John W. Redhead; Emily V. Upcott; Lucy Hulmes; Sarah Hulmes; Nadine Mitschunas; Katherine Howell; Jenny Christelow; Alexander R. Wickenden; Mike Fussell; James Plunkett; Richard F. Pywell (Journal for Nature Conservation, 2024)

Six years of demography data for 11 reef coral species - Joshua S. Madin; Andrew H. Baird; Sean R. Connolly; Maria A. Dornelas; Mariana Álvarez‐Noriega; Michael J. McWilliam; Miguel Barbosa; Shane A. Blowes; Paulina Cetina‐Heredia; Alec P. Christie; Vivian R. Cumbo; Marcela Diaz; et al. (Ecology, 2023)
Scleractinian corals are colonial animals with a range of life‐history strategies, making up diverse species assemblages that define coral reefs. We tagged and tracked ~30 colonies from each of 11 species during seven trips spanning 6 years (2009–2015) to measure their vital rates and competitive interactions on the reef crest at Trimodal Reef, Lizard Island, Australia. Pairs of species were chosen from five growth forms in which one species of the pair was locally rare (R) and the other common (C). The sampled growth forms were massive ( Goniastrea pectinata [R] and G. retiformis [C]), digitate ( Acropora humilis [R] and A. cf. digitifera [C]), corymbose ( A. millepora [R] and A. nasuta [C]), tabular ( A. cytherea [R] and A. hyacinthus [C]) and arborescent ( A. robusta [R] and A. intermedia [C]). An extra corymbose species with intermediate abundance, A. spathulata was included when it became apparent that A. millepora was too rare on the reef crest, making the 11 species in total. The tagged colonies were visited each year in the weeks prior to spawning. During visits, two or more observers each took two or three photographs of each tagged colony from directly above and on the horizontal plane with a scale plate to track planar area. Dead or missing colonies were recorded and new colonies tagged to maintain ~30 colonies per species throughout the 6 years of the study. In addition to tracking tagged corals, 30 fragments were collected from neighboring untagged colonies of each species for counting numbers of eggs per polyp (fecundity); and fragments of untagged colonies were brought into the laboratory where spawned eggs were collected for biomass and energy measurements. We also conducted surveys at the study site to generate size structure data for each species in several of the years. Each tagged colony photograph was digitized by at least two people. Therefore, we could examine sources of error in planar area for both photographers and outliners. Competitive interactions were recorded for a subset of species by measuring the margins of tagged colony outlines interacting with neighboring corals. The study was abruptly ended by Tropical Cyclone Nathan (Category 4) that killed all but nine of the more than 300 tagged colonies in early 2015. Nonetheless, these data will be of use to other researchers interested in coral demography and coexistence, functional ecology, and parametrizing population, community, and ecosystem models. The data set is not copyright restricted, and users should cite this paper when using the data.

Widespread bleaching in the One Tree Island lagoon (Southern Great Barrier Reef) during record-breaking temperatures in 2020 - Megan K. B. Nolan; Sebastian Schmidt-Roach; Andrew R. Davis; Manuel Aranda; Emily J. Howells (Environmental Monitoring and Assessment, 2021)

Localized outbreaks of coral disease on Arabian reefs are linked to extreme temperatures and environmental stressors - Greta Smith Aeby; Emily Howells; Thierry Work; David Abrego; Gareth J. Williams; Lisa M. Wedding; Jamie M. Caldwell; Monica Moritsch; John A. Burt (Coral Reefs, 2020)
The Arabian Peninsula borders the hottest reefs in the world, and corals living in these extreme environments can provide insight into the effects of warming on coral health and disease. Here, we examined coral reef health at 17 sites across three regions along the northeastern Arabian Peninsula (Persian Gulf, Strait of Hormuz and Oman Sea) representing a gradient of environmental conditions. The Persian Gulf has extreme seasonal fluctuations in temperature and chronic hypersalinity, whereas the other two regions experience more moderate conditions. Field surveys identified 13 coral diseases including tissue loss diseases of unknown etiology (white syndromes) in Porites, Platygyra , Dipsastraea , Cyphastrea, Acropora and Goniopora ; growth anomalies in Porites, Platygyra and Dipsastraea ; black band disease in Platygyra , Dipsastraea , Acropora, Echinopora and Pavona ; bleached patches in Porites and Goniopora and a disease unique to this region, yellow-banded tissue loss in Porites . The most widespread diseases were Platygyra growth anomalies (52.9% of all surveys), Acropora white syndrome (47.1%) and Porites bleached patches (35.3%). We found a number of diseases not yet reported in this region and found differential disease susceptibility among coral taxa. Disease prevalence was higher on reefs within the Persian Gulf (avg. 2.05%) as compared to reefs within the Strait of Hormuz (0.46%) or Oman Sea (0.25%). A high number of localized disease outbreaks (8 of 17 sites) were found, especially within the Persian Gulf (5 of 8 sites). Across all regions, the majority of variation in disease prevalence (82.2%) was associated with the extreme temperature range experienced by these corals combined with measures of organic pollution and proximity to shore. Thermal stress is known to drive a number of coral diseases, and thus, this region provides a platform to study disease at the edge of corals’ thermal range.

Corals in the hottest reefs in the world exhibit symbiont fidelity not flexibility - Emily J. Howells; Andrew G. Bauman; Grace O. Vaughan; Benjamin C. C. Hume; Christian R. Voolstra; John A. Burt (Molecular Ecology, 2020)
Reef‐building corals are at risk of extinction from ocean warming. While some corals can enhance their thermal limits by associating with dinoflagellate photosymbionts of superior stress tolerance, the extent to which symbiont communities will reorganize under increased warming pressure remains unclear. Here we show that corals in the hottest reefs in the world in the Persian Gulf maintain associations with the same symbionts across 1.5 years despite extreme seasonal warming and acute heat stress (≥35°C). Persian Gulf corals predominantly associated with Cladocopium (clade C) and most also hosted Symbiodinium (clade A) and/or Durusdinium (clade D). This is in contrast to the neighbouring and milder Oman Sea, where corals associated with Durusdinium and only a minority hosted background levels of Cladocopium . During acute heat stress, the higher prevalence of Symbiodinium and Durusdinium in bleached versus nonbleached Persian Gulf corals indicates that genotypes of these background genera did not confer bleaching resistance. Within symbiont genera, the majority of ITS2 rDNA type profiles were unique to their respective coral species, confirming the existence of host‐specific symbiont lineages. Notably, further differentiation among Persian Gulf sites demonstrates that symbiont populations are either isolated or specialized over tens to hundreds of kilometres. Thermal tolerance across coral species was associated with the prevalence of a single ITS2 intragenomic sequence variant (C3gulf), definitive of the Cladocopium thermophilum group. The abundance of C3gulf was highest in bleaching‐resistant corals and at warmer sites, potentially indicating a specific symbiont genotype (or set of genotypes) that may play a role in thermal tolerance that warrants further investigation. Together, our findings indicate that co‐evolution of host–Symbiodiniaceae partnerships favours fidelity rather than flexibility in extreme environments and under future warming.

Genomic and transcriptomic signals of thermal tolerance in heat‐tolerant corals ( Platygyra daedalea ) of the Arabian/Persian Gulf - Nathan L. Kirk; Emily J. Howells; David Abrego; John A. Burt; Eli Meyer (Molecular Ecology, 2018)
Scleractinian corals occur in tropical regions near their upper thermal limits and are severely threatened by rising ocean temperatures. However, several recent studies have shown coral populations can harbour genetic variation in thermal tolerance. Here, we have extended these approaches to study heat tolerance of corals in the Persian/Arabian Gulf, where heat‐tolerant local populations experience extreme summer temperatures (up to 36°C). To evaluate whether selection has depleted genetic variation in thermal tolerance, estimate potential future adaptive responses and understand the functional basis for these corals’ unusual heat tolerance, we conducted controlled crosses in the Gulf coral Platygyra daedalea . Heat tolerance is highly heritable in this population ( h 2 = 0.487–0.748), suggesting substantial potential for adaptive responses to selection for elevated temperatures. To identify genetic markers associated with this variation, we conducted genomewide SNP genotyping in parental corals and tested for relationships between paternal genotype and offspring thermal tolerance. Resulting multilocus SNP genotypes explained a large fraction of variation in thermal tolerance in these crosses (69%). To investigate the functional basis of these differences in thermal tolerance, we profiled transcriptional responses in tolerant and susceptible families, revealing substantial sire effects on transcriptional responses to thermal stress. We also studied sequence variation in these expressed sequences, identifying alleles and functional groups of differentially expressed genes associated with thermal tolerance. Our findings demonstrate that corals in this population harbour extensive genetic variation in thermal tolerance, and heat‐tolerant phenotypes differ in both gene sequences and transcriptional stress responses from their susceptible counterparts.

Population collapse dynamics in Acropora downingi , an Arabian/Persian Gulf ecosystem‐engineering coral, linked to rising temperature - Bernhard Riegl; Matthew Johnston; Sam Purkis; Emily Howells; John Burt; Sascha C. C. Steiner; Charles R. C. Sheppard; Andrew Bauman (Global Change Biology, 2018)
As in the tropical Atlantic, Acropora populations in the southern Persian/Arabian Gulf plummeted within two decades after having been ecosystem engineers on most wave‐exposed reefs since the Pleistocene. Since 1996/1998 live coral cover in the Gulf declined by over 90% in many areas, primarily due to bleaching and diseases caused by rising temperatures. In the formerly dominant table‐coral species A. downingi , population dynamics corresponding to disturbance regimes was quantified in three transition matrices (lower disturbance pre‐1996; moderate disturbance from 1998 to 2010 and 2013 to 2017, disturbed in 1996/1998, 2010/11/12, 2017). Increased disturbance frequency and severity caused progressive reduction in coral size, cover, and population fecundity. Small size‐classes were bolstered more by partial colony mortality than sexual recruitment. Some large corals had a size refuge and resisted die‐back but were also lost with increasing disturbance. Matrix and biophysical larval flow models suggested one metapopulation. Southern, Arabian, populations could be connected to northern, Iranian, populations but this connectivity was lost under assumptions of pelagic larval duration at rising temperatures shortened to a third. Then, the metapopulation disintegrated into isolated populations. Connectivity required to avoid extinctions increased exponentially with disturbance frequency and correlation of disturbances across the metapopulation. Populations became unsustainable at eight disturbances in 15 years, when even highest theoretical recruitment no longer compensated mortality. This lethal disturbance frequency was 3‐fold that of the moderately disturbed monitoring period and 4‐fold of the preceding low‐disturbance period—suggesting ongoing shortening of the disturbance‐free period. Observed population collapse and environmental changes in the Gulf suggest that A. downingi is heading toward at least functional extinction mainly due to increasingly frequent temperature‐induced mortality events, clearly linked to climate change.

Species-Specific Coral Calcification Responses to the Extreme Environment of the Southern Persian Gulf - Emily J. Howells; Glenn Dunshea; Dain McParland; Grace O. Vaughan; Scott F. Heron; Morgan S. Pratchett; John A. Burt; Andrew G. Bauman (Frontiers in Marine Science, 2018)

Host adaptation and unexpected symbiont partners enable reef‐building corals to tolerate extreme temperatures - Emily J. Howells; David Abrego; Eli Meyer; Nathan L. Kirk; John A. Burt (Global Change Biology, 2016)
Understanding the potential for coral adaptation to warming seas is complicated by interactions between symbiotic partners that define stress responses and the difficulties of tracking selection in natural populations. To overcome these challenges, we characterized the contribution of both animal host and symbiotic algae to thermal tolerance in corals that have already experienced considerable warming on par with end‐of‐century projections for most coral reefs. Thermal responses in Platygyra daedalea corals from the hot Persian Gulf where summer temperatures reach 36°C were compared with conspecifics from the milder Sea of Oman. Persian Gulf corals had higher rates of survival at elevated temperatures (33 and 36°C) in both the nonsymbiotic larval stage (32–49% higher) and the symbiotic adult life stage (51% higher). Additionally, Persian Gulf hosts had fixed greater potential to mitigate oxidative stress (31–49% higher) and their Symbiodinium partners had better retention of photosynthetic performance under elevated temperature (up to 161% higher). Superior thermal tolerance of Persian Gulf vs. Sea of Oman corals was maintained after 6‐month acclimatization to a common ambient environment and was underpinned by genetic divergence in both the coral host and symbiotic algae. In P. daedalea host samples, genomewide SNP variation clustered into two discrete groups corresponding with Persian Gulf and Sea of Oman sites. Symbiodinium within host tissues predominantly belonged to ITS 2 rDNA type C3 in the Persian Gulf and type D1a in the Sea of Oman contradicting patterns of Symbiodinium thermal tolerance from other regions. Our findings provide evidence that genetic adaptation of both host and Symbiodinium has enabled corals to cope with extreme temperatures in the Persian Gulf. Thus, the persistence of coral populations under continued warming will likely be determined by evolutionary rates in both, rather than single, symbiotic partners.

Habitat fragmentation in coastal southern C alifornia disrupts genetic connectivity in the cactus wren ( C ampylorhynchus brunneicapillus ) - Kelly R. Barr; Barbara E. Kus; Kristine L. Preston; Scarlett Howell; Emily Perkins; Amy G. Vandergast (Molecular Ecology, 2015)
Achieving long‐term persistence of species in urbanized landscapes requires characterizing population genetic structure to understand and manage the effects of anthropogenic disturbance on connectivity. Urbanization over the past century in coastal southern C alifornia has caused both precipitous loss of coastal sage scrub habitat and declines in populations of the cactus wren ( C ampylorhynchus brunneicapillus ). Using 22 microsatellite loci, we found that remnant cactus wren aggregations in coastal southern C alifornia comprised 20 populations based on strict exact tests for population differentiation, and 12 genetic clusters with hierarchical B ayesian clustering analyses. Genetic structure patterns largely mirrored underlying habitat availability, with cluster and population boundaries coinciding with fragmentation caused primarily by urbanization. Using a habitat model we developed, we detected stronger associations between habitat‐based distances and genetic distances than E uclidean geographic distance. Within populations, we detected a positive association between available local habitat and allelic richness and a negative association with relatedness. Isolation‐by‐distance patterns varied over the study area, which we attribute to temporal differences in anthropogenic landscape development. We also found that genetic bottleneck signals were associated with wildfire frequency. These results indicate that habitat fragmentation and alterations have reduced genetic connectivity and diversity of cactus wren populations in coastal southern C alifornia. Management efforts focused on improving connectivity among remaining populations may help to ensure population persistence.

Regional changes in elastic fiber organization and transforming growth factor β signaling in aortas from a mouse model of marfan syndrome - David W. Howell; Natasa Popovic; Richard P. Metz; Emily Wilson (Cell and Tissue Research, 2014)

Spatial and temporal genetic structure of S ymbiodinium populations within a common reef‐building coral on the G reat B arrier R eef - Emily J. Howells; Bette L. Willis; Line K. Bay; Madeleine J. H. van Oppen (Molecular Ecology, 2013)
The dinoflagellate photosymbiont Symbiodinium plays a fundamental role in defining the physiological tolerances of coral holobionts, but little is known about the dynamics of these endosymbiotic populations on coral reefs. Sparse data indicate that Symbiodinium populations show limited spatial connectivity; however, no studies have investigated temporal dynamics for in hospite Symbiodinium populations following significant mortality and recruitment events in coral populations. We investigated the combined influences of spatial isolation and disturbance on the population dynamics of the generalist Symbiodinium type C2 ( ITS 1 rDNA ) hosted by the scleractinian coral Acropora millepora in the central Great Barrier Reef. Using eight microsatellite markers, we genotyped Symbiodinium in a total of 401 coral colonies, which were sampled from seven sites across a 12‐year period including during flood plume–induced coral bleaching. Genetic differentiation of Symbiodinium was greatest within sites, explaining 70–86% of the total genetic variation. An additional 9–27% of variation was explained by significant differentiation of populations among sites separated by 0.4–13 km, which is consistent with low levels of dispersal via water movement and historical disturbance regimes. Sampling year accounted for 6–7% of total genetic variation and was related to significant coral mortality following severe bleaching in 1998 and a cyclone in 2006. Only 3% of the total genetic variation was related to coral bleaching status, reflecting generally small (8%) reductions in allelic diversity within bleached corals. This reduction probably reflected a loss of genotypes in hospite during bleaching, although no site‐wide changes in genetic diversity were observed. Combined, our results indicate the importance of disturbance regimes acting together with limited oceanographic transport to determine the genetic composition of Symbiodinium types within reefs.

Historical thermal regimes define limits to coral acclimatization - Emily J. Howells; Ray Berkelmans; Madeleine J. H. van Oppen; Bette L. Willis; Line K. Bay (Ecology, 2013)
Knowledge of the degree to which corals undergo physiological acclimatization or genetic adaptation in response to changes in their thermal environment is crucial to the success of coral reef conservation strategies. The potential of corals to acclimatize to temperatures exceeding historical thermal regimes was investigated by reciprocal transplantation of Acropora millepora colonies between the warm central and cool southern regions of the Great Barrier Reef (GBR) for a duration of 14 months. Colony fragments retained at native sites remained healthy, whereas transplanted fragments, although healthy over initial months when temperatures remained within native thermal regimes, subsequently bleached and suffered mortality during seasonal temperature extremes. Corals hosting Symbiodinium D transplanted to the southern GBR bleached in winter and the majority suffered whole (40%; n = 20 colonies) or partial (50%) mortality at temperatures 1.1°C below their 15‐year native minimum. In contrast, corals hosting Symbiodinium C2 transplanted to the central GBR bleached in summer and suffered whole (50%; n = 10 colonies) or partial (42%) mortality at temperatures 2.5°C above their 15‐year native maximum. During summer bleaching, the dominant Symbiodinium type changed from C2 to D within corals transplanted to the central GBR. Corals transplanted to the cooler, southern GBR grew 74–80% slower than corals at their native site, and only 50% of surviving colonies reproduced, at least partially because of cold water bleaching of transplants. Despite the absence of any visual signs of stress, corals transplanted to the warmer, central GBR grew 52–59% more slowly than corals at their native site before the summer bleaching (i.e., from autumn to spring). Allocation of energy to initial acclimatization or reproduction may explain this pattern, as the majority (65%) of transplants reproduced one month earlier than portions of the same colonies retained at the southern native site. All parameters investigated (bleaching, mortality, Symbiodinium type fidelity, reproductive timing) demonstrated strong interactions between genotype and environment, indicating that the acclimatization potential of A. millepora populations may be limited by adaptation of the holobiont to native thermal regimes.

Human In Vitro Models of Ischaemic Stroke: a Test Bed for Translation - Ana Antonic; Emily S. Sena; Geoffrey A. Donnan; David W. Howells (Translational Stroke Research, 2012)

Isolation, characterisation and cross amplification of thirteen microsatellite loci for coral endo-symbiotic dinoflagellates (Symbiodinium clade C) - Line Kolind Bay; Emily J. Howells; Madeleine J. H. van Oppen (Conservation Genetics Resources, 2009)